2010
DOI: 10.3354/meps08552
|View full text |Cite
|
Sign up to set email alerts
|

Sub-surface hotspots in shallow seas: fine-scale limited locations of top predator foraging habitat indicated by tidal mixing and sub-surface chlorophyll

Abstract: The foraging habitats of 7 species of marine apex predators were observed simultaneously in a shallow sea, with continuous measurements taken of the detailed bio-physical water column characteristics to determine habitat preferences. We found the occurrence of small-scale 'hotspots', where 50% of all animals were actively foraging in less than 5% of the 1000 km of transects surveyed. By investigating a contrasting range of foraging strategies across a variety of fisheating seabirds and marine mammals, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 45 publications
3
99
0
Order By: Relevance
“…The reasons for these differences are not clear but are likely to be related to differences in regional oceanography. Small-scale, superficial and ephemeral thermal fronts develop frequently in the Celtic Sea through tidal effects and cycles of stratification and mixing [30] but are not always associated with chl-a enrichment [28,66]. By contrast, the Benguela is a major upwelling zone, in which upwelling filaments, eddies and strong vertically structured fronts manifest.…”
Section: Mesoscale Fronts and Top Predator Foragingmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for these differences are not clear but are likely to be related to differences in regional oceanography. Small-scale, superficial and ephemeral thermal fronts develop frequently in the Celtic Sea through tidal effects and cycles of stratification and mixing [30] but are not always associated with chl-a enrichment [28,66]. By contrast, the Benguela is a major upwelling zone, in which upwelling filaments, eddies and strong vertically structured fronts manifest.…”
Section: Mesoscale Fronts and Top Predator Foragingmentioning
confidence: 99%
“…Sea-surface temperature (SST) and chlorophyll-a (chl-a) imagery are most widely used [12,32], but it is questionable whether these metrics are appropriate for defining foraging habitat, particularly for piscivores [33]. Indeed, the use of chl-a imagery in shallow shelf seas could be misleading, as sub-surface chlorophyll maxima in stratified areas can present more attractive foraging opportunities than mixed waters with elevated surface chl-a [28]. By contrast, sub-surface processes occurring along thermal fronts are known to increase prey accessibility for diving predators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown the presence of methanogenic microorganisms in these particles and have suggested that methanogenic activity originates in the digestive tracts of zooplankton and in fecal pellets. Below the ice pack, subsurface peaks of phytoplankton biomass persist, called the subsurface chlorophyll maxima (Arrigo et al, 2011), which has recently been described as an important site for predator-prey interactions (Scott et al, 2010). Thus, the existence of an abundant and active zooplankton community (including protozooplankton), and therefore pellet production (Hirche and Mumm, 1992;Morata and Seuthe, 2014), may also support anaerobic methanogenesis, playing a critical role in trophic coupling.…”
Section: Pml and Haloclinementioning
confidence: 99%
“…Alternately, local foraging hotspots for a suite of marine predators sometimes exist where a highly disproportionate amount of trophic energy exchange is focused in very small areas that feature high primary production (e.g. Scott et al 2010). Given the extreme interannual variation in the productivity of the marine environment around Triangle Island, and its documented effects on consumers in this system -including the seabirds at Triangle Island (Mackas et al 2007) -we set out to test the hypotheses that: (1) interannual variation in local marine primary productivity, particularly in spring (as crudely indicated by satellite-derived phytoplankton chlorophyll concentrations) is a critical factor driving interannual variation in the breeding success of the rhinoceros auklet, a generalist forager in this system (Davies et al 2009); (2) that the effect would be due at least in part to its effects on the recruitment of a critical prey species, Pacific sandlance Ammodytes hexapterus, and thus on its availability to the auklets, as suggested previously by Bertram et al (1991) and Hedd et al (2006);and (3) that relationships between satellite-derived chlorophyll concentration and seabird success would be applicable to other consumers in the system.…”
Section: Introductionmentioning
confidence: 99%